Cooperative Learning as a Vehicle of Enhancing Social Skills in Physical Education - Magotsiou Ευμορφία; Goudas Μάριος (Inquiries in Physical Education and Sport, 2007)
Taking theoretical and empirical data into consideration, cooperative learning, if it is applied according to a particular theory and a goaled plan, may a powerful method of learning that strengthens the students’ social skills. Contrary to general education, the research related to cooperative learning in physical education is limited. Popular programs that promote cooperative learning in physical education are the Social Responsibility Model, the Sports’ Education Model, cooperative activities through Mosston’s spectrum of teaching styles, and various cooperative games. While further research seems to be necessary regarding the above models, the development of new theory-based programs is urgent. Moreover, the interventions should aim more to the encouragement of students’ cooperative skills. This goal can be easily accomplished by considering particular principles that enhance the students’ interaction as well as the benefits of cooperative learning.